Activation of mGlu2/3 receptors, a novel therapeutic approach to alleviate dyskinesia and psychosis in experimental parkinsonism. (1st November 2019) - Frouni, Imane; Hamadjida, Adjia; Kwan, Cynthia; Bédard, Dominique; Nafade, Vaidehi; Gaudette, Fleur; Nuara, Stephen G.; Gourdon, Jim C.; Beaudry, Francis; Huot, Philippe
Abstract: Selective blockade of serotonin 2A (5-HT2A ) receptors is a promising strategy to reduce L-3, 4-dihydroxyphenylalanine (l -DOPA)-induced dyskinesia and has shown efficacy in a Phase III clinical trial for dopaminergic psychosis in Parkinson's disease (PD). However, pre-clinical and clinical evidence suggest that, while this approach may be effective and well tolerated, there might be a ceiling beyond which no further therapeutic benefit might be achieved. There is mounting evidence that 5-HT2A receptors form a functional hetero-complex with metabotropic glutamate 2 (mGlu2 ) receptors, with antagonism of 5-HT2A receptors and activation of mGlu2 receptors producing similar effects on the Gi/Gq signalling ratio at the intra-cellular level. Based on this interaction between 5-HT2A and mGlu2 receptors, we hypothesised that activation of mGlu2 receptors would alleviate dyskinesia and psychosis in PD. LY-354, 740 is a selective mGlu2/3 orthosteric agonist that was previously tested in the clinic. In experiments conducted in the 6-hydroxydopamine (6-OHDA)-lesioned rat and the 1-methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine (MPTP)-lesioned marmoset, we found that mGlu2/3 activation with LY-354, 740 significantly reduced the expression of dyskinesia and psychosis-like behaviours, while simultaneously enhancingl -DOPA therapeutic benefit. Moreover, mGlu2/3 activation with LY-354, 740 attenuated the development of dyskinesia. These data indicate that activation of mGlu2/3 receptors is a therapeutic strategy that may provide relief for both motor and-non-motor treatment-related complications in PD. Highlights: We have determined the pharmacokinetic profile of LY-354, 740 in the marmoset. LY-354, 740 reducesl -DOPA-induced dyskinesia in the 6-OHDA-lesioned rat. LY-354, 740 reducesl -DOPA-induced dyskinesia in the MPTP-lesioned marmoset. LY-354, 740 reducesl -DOPA-induced psychosis in the MPTP-lesioned marmoset. LY-354, 740 does not interfere with the anti-parkinsonian action ofl -DOPA.